ANALYSIS OF SOCIO-ECONOMIC CONDITIONS OF BAMBOO CRAWINGS IN DURIN SERUGUN VILLAGE, SIBOLANGIT DISTRICT - Selly Nindi Sari Br. Sitepu; Elfayetti Elfayetti; Herdi Herdi; M. Arif M. Arif; Rosni Rosni (Tunas Geografi, 2021)
The problem in this research is the low level of income of the population so that it affects the socio- economic conditions of bamboo craftsmen in Durin Serugun Village, Sibolangit District. This study aims to determine the Socio-Economic Conditions of the bamboo craftsmen in terms of indicators (income, education and living conditions). This research was conducted in Durin Serugun Village, Sibolangit District. The population in this study are all people who work as bamboo craftsmen. The sample in this study used a purposive sampling technique. Data collection techniques in this study are direct communication techniques to the field, study documentation, observation and questionnaires. The data analysis technique used in this research is descriptive qualitative analysis. Results of this study indicate that the socio-economic conditions of the bamboo craftsman community are seen from the main income level of bamboo craftsmen as a whole, the average ranges between Rp. 1,000,000 Rp. 2,000,000 with a percentage of 71.7% with a total of 61 respondents. Apart from the main job, the side job of bamboo craftsmen is dominated by the type of work as a farmer with an average income of IDR 1,000,000 - IDR 1,500,000 with a percentage of 85% with a total of 58 respondents. Judging from the education level of bamboo craftsmen, most of the craftsmen graduated from elementary school with a percentage of 28.2%. And the condition where bamboo craftsmen live has their own home ownership status with a percentage of 80% with improved facilities.